Review of Iraq's nationwide attempts to transform medical school curricula over the last ten decades. - Alsheikh, Ghanim; Al-sheikh, Mustafa; Kadhim, Talib; Hassoon, Abbas; Rowandozi, Injam; Mustafa, Omar (Eastern Mediterranean Health Journal, 2022)
Background: The first medical college in Iraq was established in 1927, adopting a subject-based curriculum. Aims: To provide a description of undergraduate medical education curricula in Iraq and how they developed since 1927. Methods: We identified Iraqi medical schools and curricula from local and global directories. Curricular data were compared to 3 educational benchmarks (Dale's effectiveness of teaching methods, SPICES, Miller's pyramid). We searched for studies describing curricula and modernization. Results: There are 34 medical colleges in Iraq (32 with identified curricula) with a wide scope of visions and aims adopting 3 types of curriculum: subject-based (SBC) 20 (63%), integrated (IC) 10 (31%) and problem-based learning (PBLC) 2 (6%). The majority of updates were SBC to IC, with only 1 moving from SBC to PBLC. The predominant type of curriculum at the start of instruction is SBC or IC. Although PBLC and IC provide opportunities for inquiry-driven competencies in the first 3 years only, none provide such opportunities in the clinical phase (last 3 years). Conclusions: Curricular reform needs to focus on modernizing the learning process/outcomes rather than reorganization of the teaching only. A new approach is needed to provide opportunities for competence and experience to prepare doctors to deal with challenges. One such approach would be the adoption of an outcomes-based curriculum model based on domains of competence with clearly defined outcomes/competencies achievable the time of graduation. All curricula should lead to the achievement of the same outcomes.